Lysinuric protein intolerance: a rare disease with several peculiar characteristics - Kärki, Mari (fi=Turun yliopisto|en=University of Turku|, 2025)
Lysinuric protein intolerance (LPI) is a rare, recessively inherited transporter disorder affecting the transport of cationic amino acids (CAAs) lysine, arginine and ornithine in basolateral membrane in intestine and renal tubules. Practically all Finnish LPI patients share the same homozygous variant, c.895-2A > T in the SLC7A7 gene that encodes CAA transporter y+LAT-1. The loss of function of this transporter leads to reduced intestinal absorption of lysine, arginine and ornithine and their increased excretion in the urine. Renal insufficiency is a common complication and may progress to end-stage renal disease (ESRD), requiring dialysis and eventually kidney transplantation. Severe immunological and pulmonary complications may also occur. In addition, elevated plasma zinc concentrations have been described. The treatment of LPI is based on protein-restricted diet and oral L-citrulline and lysine supplementation. Because renal insufficiency has become increasingly common in patients with LPI, in study I, a cohort of 41 Finnish LPI patients was screened for renal function, oral L-citrulline doses and plasma citrulline concentrations. In study II, the bleeding disorder associated with LPI was investigated using hemostatic and fibrinolytic markers in 15 LPI patients. Lastly, in study III, plasma calprotectin and plasma zinc concentrations of 10 LPI patients were described in detail. Signs of renal dysfunction were detected in majority of LPI patients, and some patients developed renal insufficiency at an early age. Urine β2-microglobulin was a sensitive early marker of renal involvement. To date, a total of eight Finnish LPI patients had received a kidney transplant. LPI patients show moderate bleeding tendency without spontaneous bleeds. In the present study, defective primary hemostasis, coagulopathy, fibrin abnormality and hyperfibrinolysis were detected in patients with LPI. Plasma calprotectin concentration was extremely high in all. LPI patients but plasma zinc concentration was normal or only mildly elevated. There was a positive correlation between plasma zinc and plasma calprotectin concentrations. However, plasma calprotectin did not correlate with markers of renal function. Mechanism of hypercalprotectinemia in LPI remains unknown.